Pemphigus in Oxford, UK, and New Delhi, India: a comparative study of disease characteristics and HLA antigens. - Wilson, C; Wojnarowska, F; Mehra, N; Pasricha, J (1994)
A study of pemphigus in New Delhi, India, and Oxford, UK, was undertaken including 20 patients in Oxford and 50 in New Delhi. Data included clinical and histological subtypes and socio-economic data; patients were HLA typed. In New Delhi pemphigus vulgaris predominated, but in Oxford pemphigus vulgaris and pemphigus foliaceus have equal prevalence. Disease distribution with sex was the same, but age at onset was significantly lower in New Delhi (p = 0.0019). HLA typing in pemphigus vulgaris patients revealed a significant reduction in HLA-DR2 in New Delhi (p = 0.0008) and Oxford (p = 0.09). A small increase in HLA-DR1 and -DR4 was found in both groups and, in males only, a subtle increase in HLA-DR6 and reduction in HLA-DR3. No differences were found in the class I antigens. Thus there are striking differences in the types of pemphigus between the two populations, yet the genetic predisposition is the same.